2022
DOI: 10.19173/irrodl.v23i3.6178
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Intention to Take E-Learning Courses During the COVID-19 Pandemic: A Protection Motivation Theory Perspective

Abstract: This study proposes a new model for integrating the protection motivation theory (PMT) with the technology acceptance model (TAM) to explore factors affecting students’ intention to attend e-learning courses during the COVID-19 pandemic. A total of 432 valid responses to an online questionnaire were received from freshmen students studying in universities in Vietnam and Taiwan. Structural equation modeling was used to evaluate the proposed research model and test the hypotheses, and model evaluation reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(41 citation statements)
references
References 45 publications
(72 reference statements)
2
34
1
4
Order By: Relevance
“…Although the mediating role of human attitude in the relationship between PV and human intention has not been established in some previous studies (Nguyen and Tang, 2022), our study demonstrated the mediating role of WFHRA in this relationship. Such differences can be brought about by differences in human awareness about the COVID-19 pandemic at each different stage (Maison et al, 2021;Perrotta et al, 2021).…”
Section: Hypothesis Testingcontrasting
confidence: 55%
See 4 more Smart Citations
“…Although the mediating role of human attitude in the relationship between PV and human intention has not been established in some previous studies (Nguyen and Tang, 2022), our study demonstrated the mediating role of WFHRA in this relationship. Such differences can be brought about by differences in human awareness about the COVID-19 pandemic at each different stage (Maison et al, 2021;Perrotta et al, 2021).…”
Section: Hypothesis Testingcontrasting
confidence: 55%
“…Between the two PMT factors, PV was found to have a slightly higher impact on WFHI than PS. In contrast, in a study on students' e-learning intention during the COVID-19 pandemic, Nguyen and Tang (2022) indicated that PS has a stronger impact on students' intentions. This difference could be due to the changing pandemic situation and the growth in the vaccination rate.…”
Section: Hypothesis Testingmentioning
confidence: 86%
See 3 more Smart Citations